Molecular and Pathotype Identification of Potato Cyst Nematodes - Mulyadi Mulyadi; Siwi Indarti; Bambang Rahayu T.P.; B. Triman (Jurnal Perlindungan Tanaman Indonesia, 2014)
In Indonesia, potato cyst nematode (PCN) was first reported in Bumiaji, Kota Batu, East Java by PT Syngenta and was identified as Globodera rostochiensis. Based on the surveillances, G. rostochiensis were also found in Batur, Banjarnegara, and Kejajar, Wonosobo, and Pangalengan, Bandung. In addition, in Batur, Banjarnegara, another species which was identified as G. pallida was found. The aim of this research were to identify the species of PCN using molecular method, pathotype identification, and to study the distributions of PCN especially in Java. The PCN are collected from potato planting areas in Kota Batu, East Java; Wonosobo and Banjarnegara, Central Java; and Pangalengan, Bandung, West Java. PCN were extracted and isolated from soil, and then identified by  morphological and molecular analysis. PCN were found in potato planting areas in Kota Batu, East Java; Wonosobo and Banjarnegara, Central Java; and Pangalengan, West Java. Based on the morphological characters, molecular method, and the differential host test, the PCN identified as G. rostochiensis are amplified an approximately 434 bp with pathotype Ro2.